Economic Insights into the Influence of Price, Brand Identity, and Perceived Benefits on Purchase Decisions - Huda, Raden Muhammad Syamsul; Oetarjo, Mas; Yani, Muhammad (Yayasan Riset dan Pengembangan Intelektual, 2024)
on purchasing decisions. The sampling technique in this research used the Accidental Sampling method by distributing questionnaires to 80 respondents. The data analysis method used several statistical tests: research instrument testing (validity and reliability testing) and hypothesis testing. The research results show that: (1) price positively influences purchasing decisions. (2) brand identity has a positive influence on purchasing decisions. (3) perceived benefits have a positive influence on purchasing decisions.